CONSUMPTION PATTERNS OF THE MILLENIAL GENERATION IN ONLINE SHOPPING (E-COMMERCE) DURING THE COVID-19 PANDEMIC - Hilma Farhani; R Raihan; Ratih Ayu Sekarini (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2022)
In 2020-2021 is a historical time for the whole world, this is based on the whole world is experiencing a period of pandemicc covid 19. Pandemic covid 19 that occurs globally, of course, has an impact on various sectors, one of which is the economic sector. The COVID-19 disease has caused an economic shock, both individually, in households, small, medium and large micro & macro companies, not only in Indonesia but even affect the economy of other countries. This has the effect of changing activity patterns shopping that people usually buy needs directly to the store or offline for shopping buying daily necessities to shopping online, current consumption patterns are starting change from buying goods by seeing or trying in person at the shop/place to buy the product only based on sufficient information without trying/feeling the product. The purpose of this study is to provide information about the conditions that occur in changes in consumption patterns in consumer behavior during the COVID-19 pandemic, especially in millennial generation. The research method used is a quantitative method. Research result shows consumption patterns on indicators looking for information on goods or services online. Based on the results of the study, it is concluded that there is a change in the consumption pattern of generations millennials during the covid-19 epidemic on indicators looking for information, using and buy on e-commerce services.